Measuring Energy Expenditure in extracorporeal lung support Patients (MEEP) – Protocol, feasibility and pilot trial. Issue 1 (February 2018) - Wollersheim, T.; Frank, S.; Müller, M.C.; Skrypnikov, V.; Carbon, N.M.; Pickerodt, P.A.; Spies, C.; Mai, K.; Spranger, J.; Weber-Carstens, S.
Summary: Purpose: Indirect calorimetry (IC) is the gold standard for measuring energy expenditure (EE). Due to O2 uptake and CO2 removal by both the extracorporeal lung support (ECLS) membrane and the lungs, a conventional IC is not feasible and no data available. Our MEEP (Measuring Energy Expenditure in ECLS Patients) protocol enables the determination of the REE in patients with ECLS, the comparison to patients without ECLS, and accuracy assessment of estimating equations. Methods: In the MEEP protocol, a conventional IC is performed and extended by a calculation of the O2 uptake and the CO2 elimination by the ECLS membrane. Sum O2 uptake and CO2 elimination were used in the equation of Weir to calculate EE. We included 20 patients with ARDS on veno-venous (vv)-extracorporeal membrane oxygenation (ECMO) treatment, and 20 matched ARDS patients without ECLS as control. EE measurements were compared to the most prevalent predicting equations for EE. Results: The new MEEP-protocol was shown to be feasible. None of the estimating equations matched the measured EE. Measured EE values did not significantly differ between the ARDS patients with vv-ECMO (2013 kcal/d [1786/2333]) and ARDS patients without ECLS (1857 kcal/d [1602/2085]) (p = 0.165). The blood flow through the vv-ECMO itself did not influence the EE. Conclusion: Using the MEEP protocol, EE becomes easily measurable in patients with ECLS. We recommend the implementation of sequential measurements of EE in the critically ill, especially for patients with ECLS, but also for those without, in order to improve goal directed nourishment.